If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2x + -3) = -7 Reorder the terms: 7(-3 + -2x) = -7 (-3 * 7 + -2x * 7) = -7 (-21 + -14x) = -7 Solving -21 + -14x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -14x = -7 + 21 Combine like terms: -21 + 21 = 0 0 + -14x = -7 + 21 -14x = -7 + 21 Combine like terms: -7 + 21 = 14 -14x = 14 Divide each side by '-14'. x = -1 Simplifying x = -1
| x(16-x^2)^1/2 | | -10+v-17v=4 | | 24-2x=24 | | -5(-2+x)=25 | | (.5x+5)+[.5(.5x+5)+5]+.75[.5(.5x+5)+5]+5=0 | | b/45=8/9 | | 35=10+4t | | 2y=-19/33 | | a/32=9/16 | | 30=0.75x | | 3(4x-5)+2=4x-11 | | x^2-4x+120=180 | | X/515 | | 6w-11w=20 | | 7x-10=-70+2x | | -15+x-9-6=12x-8 | | 5(l-4)=60 | | -25w=q | | 6z^3-6z=0 | | 3(x-3)+3x=4x+3 | | 6+x=-4x+51 | | 47+6k=3k-2 | | 5/6x=x/8-1 | | 3(2)-11=2(2-2)-5 | | 16=3(2b-4)-2b | | -3(2x+4)+1=-11-6x | | 2(4-3x)=82-2x | | 4(.75x+4)-3x=5 | | x^2-2=-8x | | 4x-7+6x=23 | | 7/10•1/3 | | -2(3n+4)=(-6n-6) |